Short-term reward experience biases inference despite dissociable neural correlates - Adrian G. Fischer (Nature Portfolio, 2017)
Making a good decision often requires the weighing of relative short-term rewards against long-term benefits, yet how the brain does this is not understood. Here, authors show that long-term beliefs are biased by reward experience and that dissociable brain regions facilitate both types of learning.